Structure Equation Analysis on Customer Satisfaction of Public Transport: An Empirical Study in Klang Valley Malaysia - Mei Yi, Lye; Siew Wan, Tan; Haldorai, Kavitha; Rahman, Abdul; Haque, Rasheedul; Haibin, Pan; Shengnan, Yang (International Journal of Engineering and Technology, 2018)
The purpose of this research is to determine the factors influencing international tourist satisfaction on the public rail services in Klang Valley, Malaysia. This paper provides important contribution to the Malaysian economy due to the growing number of international tourist in recent years. A mixed methodology approach via the use of phenomenological interviews and self-administered questionnaire were use. Structure equation modelling (SEM) revealed three key dimensions of public rail service attributes which is comfort, accessibility, responsiveness and safety. The result indicated that there is significant relationship between comfort, safety and accessibility. Transportation authorities can use these findings as a guide to enhance the quality of life of public rail service users in the future.Â Â Â